Answer:
- 5, 2, 9, 16 and d = + 7
Step-by-step explanation:
to obtain the first four terms substitute n = 2, 3, 4 into the recursive formula
f(1) = - 5 ← given
f(2) = f(1) + 7 = - 5 + 7 = 2
f(3) = f(2) + 7 = 2 + 7 = 9
f(4) = f(3) + 7 = 9 + 7 = 16
common difference d = 16 - 9 = 9 - 2 = 2 - (- 5) = 7
Answer:
n=25
Step-by-step explanation:
-3n-8=-83
-3n-8+8=-83+8
-3n=-75
n=25
Answer:
v= 13
w= -32
Step-by-step explanation:
2v+6w=-36
5v+2w=1
2w= 1-5v
2v+ (3)(1-5v)= -36
2v+3-15v= -36
3-13v =-36
3--36= 13v
39= 13v
13 = V
5×13+2w=1
65+2w=1
1-65= 2w
-64=2w
-32=w
Answer:
32.8937 units
Step-by-step explanation:
So, we can imagine this as a right triangle with a length of 11 (THe change of the X's) and the height being 31 (Change of the Y's)
Then we use pythagorean therom to find the hypotenuse (the length)
11^2 + 31^2 = c^2
121+961 = C^2
1082 = c^2
32.8937units